Histopathological Spectrum of Gall Bladder Lesions in A Tertiary Care Hospital in The Malwa Belt: A Hospital Based Study - Thukral, Shaffy; Roychoudhury, Arnav Kr; Bansal, Nidhi; Rani, Ekta (Annals of Pathology and Laboratory Medicine, 2018)
Introduction: Gallbladder stones are commonest disorder among gall bladder lesions and are usually asymptomatic. Its frequency in cholecystectomy specimens is not clear. The aim of this study was to report the morphological variants and frequency of different lesions in cholecystectomy specimens. Objective: To study the various histopathological spectrum of gall bladder lesions. Materials And Methods: In present study we have studied total 141 cases of gall bladder lesion during the period of 6 months from April 2017 to October 2017 in the Dept. of Pathology at Adesh Institute of Medical Sciences and Research, Bathinda. Results: Benign lesions of gall bladder outnumbered the malignant ones with non-neoplastic lesions accounting for 93.6% (132 cases) with chronic calculous cholecystitis contributing the majority of the non-neoplastic lesions (49.64%) followed by cholesterolosis (22.69%), acalculous cholecystitis (4.96%), followed by gangrenous and xanthogranulomatous cholecystitis. Females were predominantly affected in the present study with total 107 cases out of 141 cases-75.8% cases. Most of the non-neoplastic lesions of the gall bladder lesions are common in 3rd, 4th and 5th decades of life. Neoplastic lesions of the gall bladder were common in 5th, 6th and 7th decades of life. Out of 141 cases 5 cases are of adenocarcinoma of gall bladder-3.5% of all cases. The mean age of patient with adenocarcinoma of gall bladder is 60.8 years. Conclusion: Gall bladder lesions were common indication for surgical intervention and pathological evaluation. Most of them were inflammatory lesions with cholelithiasis, however thorough examination is important as these lesions may progress to fatal malignancies.